Optimal AGC regulator for multi-area interconnected power systems with parallel AC/DC links. Issue 1 (31st December 2016) - Singh, Omveer; Nasiruddin, Ibraheem
Abstract: The problem of simultaneous tuning of the automatic generation control (AGC) regulator's gains of multi-area interconnected power system is carried out in this manuscript. Based on the types of area interconnections, a power system model consisting of reheat turbines is investigated by two test cases for the AGC study. In one of the test case AC link is used as area interconnection, whereas the parallel combination of AC/DC links is used as area interconnection in other test case. Each test case control area is consisting of plants with reheat thermal turbines. Genetic algorithm (GA) is used to globally optimize the gains of proportional integral-based AGC regulators with simultaneous optimization of frequency bias coefficient and tie-line power flows. The dynamic response curves are obtained for various system states with the implementation of designed GA-based AGC regulators considering 1% load perturbation in one of the areas. The conventional AGC regulators are also developed using the popularly known Ziegler–Nichols technique. The investigations carried out demonstrate the superiority of proposed regulators over the conventional AGC regulators. The incorporation of DC link in parallel with AC link as an area interconnection has also exhibited favorable effect on dynamic response of the system.